Strategies for Communicating Health and Safety Information on Construction Sites in Nigeria - Alara, Samuel Abiodun; Inuwa, Ibrahim Ibrahim (Proceedings of the International Conference on Civil Infrastructure and Construction (CIC), 2020)
The construction industry (CI) has earned the notoriety of being a risky or profoundly unsafe industry. Studies have credited the majority of the mishap on construction sites to poor communication of health and safety (H&S) information among all the parties engaged in construction activities. The study assessed strategies for communicating H&S information on construction sites and evaluates factors influencing the choice of communication strategies for H&S information on construction sites. The data for the investigation were gotten using multiple-choice questionnaire administered on 20 construction sites domicile in Abuja, Nigeria. A sum of one hundred (100) questionnaire were administered to respondents; out of which eighty-five (85) were returned speaking to 85% reaction rate. Data received were analyzed using descriptive and inferential statistics at 95% degree of certainty. The study revealed that safety signs and training are most important medium of communicating H&S information on construction sites and shown that cost implication of the strategy significantly influences the choice of communication strategies for H&S information on Nigerian construction sites. The study therefore, recommends that contracting firms be duty-bound to engage signs and symbols in communicating H&S information, as communication that involves images is clearer and can be directly understood. Quantity surveyors should ensure that adequate provision is made in the bill of quantities for implementing H&S procedures on construction sites. Safety awareness ought to be incorporated in the overall procurement procedure, and workers should be consistently train and re-train on H&S procedures.